Assessment of broad-leaved forest stand management : stock densities, thinning costs and profits over a 60-year rotation period - Suzuki, Yasushi (Array, 2019)
There are many broad-leaved forests in Japan that were formerly managed for charcoal production, which have been abandoned for decades. Appropriate thinning can revitalize these forests if the cost balance of the management is positive. Two critical elements are the construction of spur roads to facilitate mechanized harvesting operations and management planning that considers stand properties such as the growing stock, species, and tree size distribution. We surveyed three abandoned former broad-leaved coppice stands; one coastal, one cool temperate and one warm temperate. The stock in all three stands exceeded 300 m3 ha-1, two- to three-fold the official forest registry data estimates. The dominant species in terms of tree numbers are Castanopsis sieboldii, Pieris japonica, and Quercus glauca. Medium-sized trees involve those well suited for firewood, i.e., Quercus acuta, Quercus glauca, Quercus serrata, etc. Each plot contained a few large trees that potentially have a high market value, e.g., Cinnamomum camphora, Zelkova serrata, Abies firma, etc. The average income from harvested trees was estimated to be 10200 JPY (Japanese Yen) m-3, whereas the thinning costs would be 3200 to 5400 JPY m-3, with the additional spur road construction costs. The management cost balance of a broad-leaved stand in a 60 year rotation was evaluated with both Net Present Value (NPV) (for interest rates of 1, 2, 3, and 4%) and Internal Rate of Return (IRR). This balance was compared with that of a typical plantation stand of Japanese cedar (Cryptomeria japonica) and of a fast-growing plantation stand of Chinese fir (Cunninghamia lanceolata). The estimated NPVs were largest for the fast-growing plantation stand, second largest for the typical plantation stand, and lowest for the broad-leaved stand with a NPV interest rate of 1 + %.